THE IMPROVEMENT OF THE DYNAMICS OF EMPTY CARS ON TRUCKS 18-100 MODEL - Savchuk, O. M.; Shatunov, O. V.; Reidemeister, O. H.; Hrechanyi, M. A.; Ryzhov, V. O.; Lukhanin, M. I. (Science and Transport Progress, 2007)
A new chart of springing complete set of freight light cart is represented 18-100 with the use of three-component wedges and subspringy skol'zunov, and also the analysis of results of alpha and train dynamic tests of different types of freight carriages of equipped on this new chart is resulted.